Strategy for Implementing Sustainable Tourism in the Development of Pringgasela Tourism Village, Pringgasela District, East Lombok Regency - Rizkia, Ahmad; Salmah, Emi; Singandaru, Adhitya Bagus (West Science Social and Humanities Studies, 2025)
This study aims to determine the strategy for implementing sustainable tourism in the development of Pringgasela Tourism Village, Pringgasela District, East Lombok Regency. The approach used in this study is a qualitative approach with descriptive methods. The data analysis method used to analyze the data in this study is a SWOT analysis tool (Strong, Weakness, Opportunity, and Threat). The results of this study found the driving factors for the Strategy for Implementing Sustainable Tourism in the Development of Pringgasela Tourism Village, Pringgasela District, East Lombok Regency, which obtained a very high category are the arrangement of a very beautiful and beautiful tourist village, the beauty of the culture displayed (Village Cultural Alunan Event), abundant water sources, having superior woven products, a location not far from the city center. The inhibiting factors that obtained a very high category are the low level of human resources in terms of education or training for the community in developing tourist villages, less than optimal tourism promotion and marketing, inadequate on-site facilities, lack of experts in managing tourist areas and lack of village government participation in terms of infrastructure, human resource training, tourism management, and cooperation with stakeholders for the development of village potential.